Coding Cell Identity of Human Skeletal Muscle Progenitor Cells Using Cell Surface Markers: Current Status and Remaining Challenges for Characterization and Isolation - Tey, Sin-Ruow; Robertson, Samantha; Lynch, Eileen; Suzuki, Masatoshi (Frontiers in Cell and Developmental Biology, 2019)
Skeletal muscle progenitor cells (SMPCs), also called myogenic progenitors, have been studied extensively in recent years because of their promising therapeutic potential to preserve and recover skeletal muscle mass and function in patients with cachexia, sarcopenia, and neuromuscular diseases. SMPCs can be utilized to investigate the mechanisms of natural and pathological myogenesis via in vitro modeling and in vivo experimentation. While various types of SMPCs are currently available from several sources, human pluripotent stem cells (PSCs) offer an efficient and cost-effective method to derive SMPCs. As human PSC-derived cells often display varying heterogeneity in cell types, cell enrichment using cell surface markers remains a critical step in current procedures to establish a pure population of SMPCs. Here we summarize the cell surface markers currently being used to detect human SMPCs, describing their potential application for characterizing, identifying and isolating human PSC-derived SMPCs. To date, several positive and negative markers have been used to enrich human SMPCs from differentiated PSCs by cell sorting. A careful analysis of current findings can broaden our understanding and reveal potential uses for these surface markers with SMPCs.